Proyek Perancangan Co-Working Space dengan Pendekatan Design Behavior oleh Konsultan Arsitektur Interior VR Architect Interior - Reginald, Verdo; Nuradhi, Maureen (KREASI, 2024)
The office is a place where the majority of people work and where a company runs. The development of the world industry has encouraged changes in old office systems to co-working spaces and co-offices. This new office system allows people to work more freely in small-scale companies or start-ups. Indonesian people are also starting to use the office system as a co-working space as one way to start their business. co-working space It has become an alternative for the community as a company office; apart from only needing a small office, it also has the public amenities required by an office, including a workable rental system. Design a co-working space This can be a VR architect’s interior design project where the office is closely related to design behavior. Design behavior that fits the method of the user carrying out certain activities or activities can increase the comfort and efficiency of those activities. The co-working space project is situated on the first floor of the Praxis building in Surabaya. Due to its central location, it offers easy and roomy access. With this design project, it is hoped that the office design and co-working space will receive more attention and use as an added value to an office, especially in the design of the co-working space. Using the design behavior approach when planning co-working spaces is intended to improve user happiness, boost productivity, and foster a more positive work atmosphere.